A comparison of wear behaviour of heat-resistant steel engine valves and TiAl engine valves. (October 2020) - Lai, Fuqiang; Qu, Shengguan; Qin, Haidi; Lewis, Roger; Slatter, Tom; Li, Xiaoqiang; Luo, Huahuan
The increasing demand for higher performance internal combustion engines has led to higher temperatures in the combustion chamber. As a result, TiAl valves have been investigated with a view to their use in a natural gas fuelled diesel internal combustion engine, taking advantage of their low density and good high-temperature resistance. In this work, comparison bench tests for traditional steel valves and TiAl valves were carried out through the use of specially designed wear testing apparatus. Compared to the traditional valves made from heat-resistant steel (X60, X85), the TiAl valves have 50% lower mass, leading to a decrease in the impact seating forces during the engine operation. With the reduction of the inertia of engine valve movement, the dynamic characteristics of the engine valve train system can be optimized. Each contact pair of valve and seat insert was tested for 3 million impact cycles. Compared to the austenitic exhaust valves (X60) tested at 700 ℃, the TiAl valve had better wear resistance and the wear loss decreased by 24.8 %. The predominant wear mechanism is considered to be a combination of oxidative wear and adhesive wear. However, for the intake valves tested at 400 ℃, the wear loss of the TiAl valve was three times higher than the martensitic intake valves (X85). The predominant wear mechanism can be identified as abrasive wear and adhesive wear. It is therefore concluded that the TiAl exhaust valve is a potential solution for a natural gas fuelled diesel.